2016
DOI: 10.1111/cpr.12277
|View full text |Cite
|
Sign up to set email alerts
|

Deconvoluting the complexity of microRNAs in autophagy to improve potential cancer therapy

Abstract: MicroRNAs (miRNAs) (small, non-coding RNAs ∼22 nucleotides [nt] in length), have been estimated to regulate in the region of 30% of human gene expression at the post-transcriptional and translational levels. They are also involved in a series of important cellular processes, such as autophagy. Autophagy is well-known to be an evolutionarily conserved lysosomal degradation process in which a cell degrades long-lived proteins and damaged organelles. Recent evidence has shown that miRNAs can function as either on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 81 publications
1
7
0
Order By: Relevance
“…On the other hand, miR-27b-3p might prevent the autophagic degradation of impaired mitochondria 45 . The dual effect of miR-27b-3p is possibly tissue- or cellular context-dependent, which is consistent with other miRNAs 46 . Apart from many targets including PINK1, FOXO1, PPARγ and Apaf-1 investigated before, MKNK2, GREM1 and EEF1A1 that might be potential targets of miR-27b-3p were revealed in the regulatory network of MELAS pathogenesis.…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, miR-27b-3p might prevent the autophagic degradation of impaired mitochondria 45 . The dual effect of miR-27b-3p is possibly tissue- or cellular context-dependent, which is consistent with other miRNAs 46 . Apart from many targets including PINK1, FOXO1, PPARγ and Apaf-1 investigated before, MKNK2, GREM1 and EEF1A1 that might be potential targets of miR-27b-3p were revealed in the regulatory network of MELAS pathogenesis.…”
Section: Discussionsupporting
confidence: 87%
“…Because autophagy incidence is inside cells, the present study evaluates the expression of miRNAs in BC tissue samples. miRNAs have several roles in the regulation of autophagy processes such as recycling, degradation, fusion, vesicle nucleation, vesicle elongation, and induction ( 123 ).…”
Section: Mirnas Role In Autophagy and Bcg Therapymentioning
confidence: 99%
“…We therefore also performed literature searches for links between autophagy and the other candidates from our list of predicted oxidative stress-modulated miRNAs shown in Table 3 . We found that several of these miRNAs have been implicated in autophagy regulation, that is, miR-15a, miR-20a/b, miR-23a/b, miR-29a, miR-106a/b, miR-195, and miR-590-3p [ 67 , 70 , 73 , 77 81 ]. For example, miR-29a targets the product of the essential autophagy-related gene ATG9A as well as that of the master transcriptional regulator of lysosomal biogenesis and autophagy, TFEB [ 77 ].…”
Section: Resultsmentioning
confidence: 99%